2009
DOI: 10.1111/j.1471-3802.2009.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of environmental interventions to improve child language outcomes for children with or at risk of primary language impairment

Abstract: We recommend you cite the published version. The publisher's URL is http://dx.doi.org/10.1111/j. 1471?3802.2009.01119.x Refereed: YesThe definitive version is available at www3.interscience.wiley.com Disclaimer UWE has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material. UWE makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…For example, Zeng et al 30 found that 'teaching sessions' that were part of an intervention were rarely described and characteristics of the dosage were not always transparent. Pickstone et al 35 commented on the variety of terminology and the lack of descriptive detail used to describe interventions. Furthermore, Pickstone et al 35 concluded that interventions can have differential effects on subgroups of children and/or families and also that the effects of any particular component of an intervention are rarely tested and the effects of individual components are difficult to extract from research using complex interventions.…”
Section: What Do We Know About These Interventions/services?mentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Zeng et al 30 found that 'teaching sessions' that were part of an intervention were rarely described and characteristics of the dosage were not always transparent. Pickstone et al 35 commented on the variety of terminology and the lack of descriptive detail used to describe interventions. Furthermore, Pickstone et al 35 concluded that interventions can have differential effects on subgroups of children and/or families and also that the effects of any particular component of an intervention are rarely tested and the effects of individual components are difficult to extract from research using complex interventions.…”
Section: What Do We Know About These Interventions/services?mentioning
confidence: 99%
“…Pickstone et al 35 commented on the variety of terminology and the lack of descriptive detail used to describe interventions. Furthermore, Pickstone et al 35 concluded that interventions can have differential effects on subgroups of children and/or families and also that the effects of any particular component of an intervention are rarely tested and the effects of individual components are difficult to extract from research using complex interventions. The study by Landry et al 36 was a noted exception to this.…”
Section: What Do We Know About These Interventions/services?mentioning
confidence: 99%
See 3 more Smart Citations